2013
DOI: 10.1002/ajim.22217
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid persistent lower respiratory symptoms and posttraumatic stress disorder 5–6 years post‐9/11 in responders enrolled in the World Trade Center Health Registry

Abstract: Outcomes in comorbid responders were similar to or more severe than in comorbid survivors. Health care and disaster relief providers must suspect comorbid illness when evaluating responders' respiratory or mental illnesses and consider treatment for both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 32 publications
4
41
1
Order By: Relevance
“…Half of the enrollees with persistent LRS also had at least one mental health condition. Comorbid LRS and mental illness have been reported in rescue/recovery workers by other WTC disaster investigators10 14 16 18 and in Registry surveys from 2003–2004 and 2006–2007 among workers and residents 4 15 17 27. This study extends those findings to demonstrate that the co-occurrence of respiratory and mental health illness has continued for at least 10 years after the disaster and that reported persistent LRS were highly associated with probable GAD, depression and PTSD separately and in combination.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Half of the enrollees with persistent LRS also had at least one mental health condition. Comorbid LRS and mental illness have been reported in rescue/recovery workers by other WTC disaster investigators10 14 16 18 and in Registry surveys from 2003–2004 and 2006–2007 among workers and residents 4 15 17 27. This study extends those findings to demonstrate that the co-occurrence of respiratory and mental health illness has continued for at least 10 years after the disaster and that reported persistent LRS were highly associated with probable GAD, depression and PTSD separately and in combination.…”
Section: Discussionsupporting
confidence: 76%
“…Comorbid LRS and mental illness have been associated with greater decreased QoL than LRS alone in rescue/recovery workers, local area workers and residents 15 17 19. Reported persistent LRS in this study were significantly associated with ≥14 days of poor physical and with ≥14 days of poor mental health, even while controlling for the number of coexisting mental health conditions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Prior Registry studies have identified relationships between PTSD and other mental health conditions and both persistent and more frequent lower respiratory symptoms and poorly controlled asthma [6,30,31]. Potential pathways that link mental health conditions to increased asthma morbidity may be biological as well as behavioral.…”
Section: Discussionmentioning
confidence: 99%
“…We now understand that postdisaster mental health issues in adults and children were common and, importantly, also often chronic, including symptoms of posttraumatic stress disorder, anxiety, and depression related not only to the immediate trauma, but also to the longerterm recovery and rebuilding efforts and medical illnesses (16,(37)(38)(39)(40)(41)(42)(43). Comorbidity of mental and physical health issues compounds complexity of diagnosis and management.…”
Section: Special Article What We Have Learned About Health Effectsmentioning
confidence: 99%